Integration of Local Wisdom in Mathematics Learning: Systematic Literature Review - Magdalena Dhema; Mohammad Fitri; Maria Aprilia Venerani Gokun (Universitas Muhammadiyah Malang, 2026)
The integration of local wisdom in mathematics learning is gaining increasing attention as it helps bridge abstract mathematical concepts with students’ contextual experiences. Learning that incorporates local cultural values, practices, and artifacts not only enhances conceptual understanding but also strengthens cultural identity and the relevance of learning in everyday life. However, existing studies on this topic remain scattered, with diverse approaches, findings, and levels of effectiveness. Therefore, a systematic literature review is needed to identify research trends, implementation forms, and the impacts of integrating local wisdom in mathematics learning. This study aims to systematically analyze the integration of local wisdom in mathematics learning using a Systematic Literature Review (SLR) combined with bibliometric analysis. The data were obtained from the Scopus database, covering publications from 2019 to 2026 using the keyword